Prenatal care according to professional records from the pregnant woman's book - Lígia Laura de Sousa Castro; Isabelly Gomes de Oliveira; Raylla Araújo Bezerra; Leilane Barbosa de Sousa; Saiwori de Jesus Silva Bezerra dos Anjos; Lydia Vieira Freitas dos Santos (Universidade Federal de Santa Maria, 2020)
Objective: To describe prenatal care according to the professional records from the pregnant woman's book. Method: A quantitative study carried out with postpartum women of a philanthropic maternity located in a municipality in the inland of the State of Ceará. The sociodemographic data were collected in an interview and the prenatal information was obtained from the pregnant woman's book. Data was analyzed by descriptive statistics. Results: 52 women between 15 and 40 years old participated in the study. There were flaws in the recording of information, the most serious being related to laboratory tests and nutritional evaluation of the pregnant woman. Final Considerations: A change in professional conduct is necessary, through qualification about prenatal care and frequent monitoring by the municipal health managers, since recording of information obtained during health care visits makes it possible to carry out appropriate follow-up during childbirth and the postpartum period.